Primary data preparation for management accounting purposes (Путеводитель предпринимателя, 2020)
The article analyses management accounting as a relations of production between company employees, which include information preparation, checking its validity, processing it and transferring it to a user. The analysis includes organization of employees relations for primary control of deviations in production process.